Scalable Ontological EAI and e-Business Integration - Lemcke, Jens (KIT Scientific Publishing, 2010)
Integration of enterprise applications (EAI) and e-business integration are time-consuming and expensive. This thesis proposes pattern mining to determine identical object classes. Processes are integrated based on declared integration goals and known software behavior. A model-driven approach ensures consistent use of behavioral knowledge from development in integration. The contributions were applied to the CCTS Modeler Warp 10 and SAP NetWeaver CE (composition environment) developed at SAP.
English
Keywords: business process integration; model-driven software development; semantic Web services; data integration; frequent itemset mining